1997
DOI: 10.1089/jir.1997.17.369
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Fas and Fas Ligand in Renal Grafts with Acute and Chronic Rejection in the Rat Model

Abstract: The Fas system-based rejection mechanism has not been studied well in terms of cytotoxic T cell activity in graft rejection. We investigated the Fas and Fas ligand level in renal grafts with acute and chronic rejection in a rat model using semiquantitative reverse transcription-polymerase chain reaction (RT-PCR). Fas ligand in renal allografts was detected as early as 1 day after transplantation in an acute rejection model. It was highly expressed at day 4 and began to decline at day 6 after transplantation. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…On day 9, we observed a massive necrosis of hepatocytes and the decreased number of apoptotic cells, suggesting irreversible hepatic failure progressed probably after the peak of acute rejection. These results are similar to previous reports on acute kidney allograft rejection [28], which showed an increased expression of Fas ligand preceding the peak of injury. They demonstrated that the expression of Fas ligand depended on the number of infiltrating leukocytes, which decreased in the late phase of acute rejection.…”
Section: Fig 3-continuedsupporting
confidence: 92%
“…On day 9, we observed a massive necrosis of hepatocytes and the decreased number of apoptotic cells, suggesting irreversible hepatic failure progressed probably after the peak of acute rejection. These results are similar to previous reports on acute kidney allograft rejection [28], which showed an increased expression of Fas ligand preceding the peak of injury. They demonstrated that the expression of Fas ligand depended on the number of infiltrating leukocytes, which decreased in the late phase of acute rejection.…”
Section: Fig 3-continuedsupporting
confidence: 92%
“…During acute rejection, both an increase and a decrease in expression of CD95 in human renal tubular epithelial cells have been described [26][27][28]. The role and engagement of CD95-CD95 ligand pathway inhibitor FLIP during acute rejection in renal transplant recipients is not clarified yet.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted using a Tri Reagent isolation kit (Molecular Research Center, Inc., Cincinnati, OH), according to the manufacturer's instructions, and dissolved in diethylpyrocarbonatetreated water and quantified by spectrophotometer. Reverse transcription of RNA from sample tissues, followed by polymerase chain reaction (PCR), was used to detect Fas and FasL gene expression [18]. cDNA was synthesized from total RNA in approximately 100 ng in 20 ml of reaction mixture using a first strand cDNA kit (Boehringer Mannheim, Mannheim, Germany), including 1× PCR buffer, 5 mM MgCl 2 , 1 mM dNTP, 50 U RNase inhibitor, 20 U AMV reverse transcriptase, and 1·6 mg oligo(dT) 15 as a primer.…”
Section: Rna Isolation and Reverse Transcriptase-polymerase Chain Reamentioning
confidence: 99%
“…Alternatively, CD8 þ T cells activated by donor class I antigen may be trapped in the liver and eliminated by receiving a signal to undergo apoptosis in the transplanted liver graft [14,15]. There is recent experimental evidence that manipulation of the Fas/Fas ligand (FasL) system might provide this type of apoptosis signal to induce allospecific immunosuppression [16][17][18].…”
Section: Introductionmentioning
confidence: 99%